Feeding history affects cub survival of young breeding blue foxes (Alopex lagopus), a field study - Koskinen, Nita; Tauson, Anne-Helene; Sepponen, Juhani; Rekilä, Teppo (International Fur Animal Scientific Association (IFASA), 2008)
Introduction: In recent years selective breeding in blue fox farming in Finland has focused on producing large and heavy animals. At present blue foxes are fed unrestricted during the growing - furring period, independent of dietary energy concentration. Ad libitum feeding hence often leads to animals being very fat or even obese at the time of pelting. Fur farmers in Finland have been alerted since 1990, because the number of cubs born has not been as expected. Among first-year breeding blue foxes litter size has decreased during the years 1995-2007. Recent data suggest that blue fox vixens being selected for breeding purposes during the late summer, and then being reared on a restricted feeding regimen, have better reproduction results when compared to vixens reared on unrestricted feeding (Koskinen et al., 2006, Koskinen et al. 2007). Similar results were shown in Norwegian field studies (Sanson and Ahlstrøm 2005). These findings are in good agreement with previous findings in another seasonal animal, the mink (Tauson & Aldén 1984, Tauson, 1993). The objectives of this field study were to: determine if the time when blue fox females are selected for breeding and body conditioning affect the breeding result; to determine the correlation between body weight of artificially inseminated blue fox females, breeding results and cub survival.
Keywords: Ko; eloonjäänti; sinikettu; turkiseläimet; pennut; ruokinta; jalostus; furbearing animals; feeding; breeding; survival; blue fox; cubs